KAJIAN PENERAPAN PRODUKSI BERSIH DI AGROINDUSTRI KOPI WULAN, KECAMATAN MAESAN, KABUPATEN BONDOWOSO - Elida Novita; Khotijah Khotijah; Dian Purbasari; Hendra Andiananta Pradana (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Wulan Coffee Agroindustry is one of agroindustries in region of Bondowoso that applies the semi-wet method and it has potential to be certified by Geographical Indications (IG). The wastes of arabica coffee processing at Wulan Coffee Agroindustry is directly thrown to the surrounding environment without being repaired first, because of that, it is worried that can affect human health and the environment. Therefore, further treatment is necessary to reduce the impact of waste pollutions and improve the efficiency of processing by using cleaner production technology. This study aimed to examine the priority alternative of cleaner production at Wulan Coffee Agroindustry. The method used in this study is descriptive quantitative with mass balance analysis, energy balance analysis, feasibility analysis, and priority analysis of cleaner production application using the method of AHP (Analytical Hierarchy Process). The waste management alternative in the Wulan Coffee Agroindustry were coffee pulp waste processing i.e. cascara tea, briquettes, and animal feed, also the waste water of coffee processing as biogas. The cleaner production applied in the Wulan Coffee Agroindustry had alternatives likes coffee green bean, coffee powder, and cascara tea. It was the priority scale to be applied because technically factor and financial factor consist of NPV, IRR, B/C ratio, and PBP were Rp 1.211.88.689; 49%; 6.27, and 0.76 or 9 month. Therefore, the result of AHP analysis using expert choice application showed that cascara tea was the priority alternative of cleaner production application with value of 15,4. Keyword: arabica coffee, assessment, Bondowoso, feasibility analysis, waste utilization